Revitalization of an IoT-Based Greenhouse as a Solution for Precision and Sustainable Agriculture - Renita Kawuryan; Prapdopo Prapdopo; Umi Zunaidah; ST Nurhasanah; Tandi Kadang; Aulia Zahra Ramadhani (CV. Era Digital Nusantara, 2026)
The community partnership program was designed to revitalize the greenhouse at the Taman Teknologi Pertanian (TTP) Kutai Kartanegara through the integration of Internet of Things (IoT)-based automation and frugal innovation. The initiative was implemented collaboratively by Politeknik Negeri Samarinda using a participatory action approach that actively involved local farmers throughout the planning, implementation, and evaluation processes. The program was executed in four structured phases: (1) Preliminary Assessment and Consultation, which identified inefficiencies in the existing sprinkler irrigation system; (2) Design and Prototyping, which developed a low-cost screw-adjusted drip irrigation model allowing precise water control; (3) IoT System Development, which incorporated DHT sensors, relay switches, and smartphone-based control for real-time monitoring; and (4) Installation and Training, which ensured full system implementation and capacity building among participating farmers. The results showed a successful transformation of the greenhouse into an automated and efficient agricultural environment. The new system allowed both manual and automatic operation, improving water-use efficiency and reducing maintenance efforts. Moreover, the participatory training strengthened farmers’ digital and technical competencies, enabling them to manage and maintain the IoT-based system independently. The program’s outcomes highlight how affordable, context-appropriate technology, when supported by community participation and institutional collaboration, can contribute to sustainable and inclusive agricultural innovation. Ultimately, this initiative serves as a model for integrating low-cost digital technology into smallholder farming systems, promoting productivity, resilience, and the digital transformation of rural agriculture in Indonesia.